Fast Forging: A new SPD method to synthesize Mg-based alloys for hydrogen storage. (13th March 2020) - de Rango, Patricia; Fruchart, Daniel; Aptukov, Valery; Skryabina, Nataliya
Abstract: Magnesium alloys and more especially the Mg2 Ni compound remain of high interest for reversible hydrogen storage, in spite of high temperature and poor sorption kinetics. Conventionally the Mg-based hydrides are prepared as activated powders by using the High Energy Ball-Milling technique, as well involving some amounts of activating additives. We have developed the technique of Fast Forging (FF) of mixed Mg and Ni samples. Early results show that when processing at low or medium temperatures the FF process acts better as other Severe Plastic Deformation (SPD) techniques. When processing at a temperature high enough, the formation of a mixture of Mg and binary Mg2 Ni was promptly achieved by FF. XRD and first hydrogenation kinetics illustrate well the two different sides of the FF-technique that can be compared to Ball-Milling and Mechanical Alloying procedures, respectively. Graphical abstract: XRD powder patterns of the Mg-22 wt% Ni sample after submitted to Fast Forging at: a - 210 °C, revealing no phase transformation, b - 480 °C, where major parts of the starting elements form significant amounts Mg2 Ni. Image 1 Highlights: Fast-Forging synthesis Mg/Mg2 Ni alloys from Mg and Ni powders. At low-to-medium temperatures, the process operates as Severe Plastic Deformation. At high temperature, lower than the Mg–Ni eutectic, a complete alloying of metals was achieved. Numerical estimate over-heating from mechanical energy and hydrogenation enlighten processes.